KORELASI MOTIVASI DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN - Helti Sondang Manulang; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This research aims to determine the correlation between work motivation and loyalty to employee performance. The research method used in this research is a literature study (qualitative). Sources of data in this study were obtained from library sources such as journals, theses, e-books, as well as information from the internet and the official website listed on Google. The results obtained in this study are that several companies still lack motivation which results in many employees leaving the company without the reasons, therefore the company must pay attention to each employee so that employees have good work motivation so that the quality of employee performance also increases.